PROLIDASE: A Review from Discovery to its Role in Health and Disease - Eni-Aganga, Ireti; Lanaghan, Zeljka Miletic; Balasubramaniam, Muthukumar; Dash, Chandravanu; Pandhare, Jui (Frontiers in Molecular Biosciences, 2021)
Prolidase (peptidase D), encoded by the PEPD gene, is a ubiquitously expressed cytosolic metalloproteinase, the only enzyme capable of cleaving imidodipeptides containing C-terminal proline or hydroxyproline. Prolidase catalyzes the rate-limiting step during collagen recycling and is essential in protein metabolism, collagen turnover, and matrix remodeling. Prolidase, therefore plays a crucial role in several physiological processes such as wound healing, inflammation, angiogenesis, cell proliferation, and carcinogenesis. Accordingly, mutations leading to loss of prolidase catalytic activity result in prolidase deficiency a rare autosomal recessive metabolic disorder characterized by defective wound healing. In addition, alterations in prolidase enzyme activity have been documented in numerous pathological conditions, making prolidase a useful biochemical marker to measure disease severity. Furthermore, recent studies underscore the importance of a non-enzymatic role of prolidase in cell regulation and infectious disease. This review aims to provide comprehensive information on prolidase, from its discovery to its role in health and disease, while addressing the current knowledge gaps.